Diversity and Inclusion Policy Strategies to Optimize Leader Support for Enhancing Team Creativity in Starred Hotels in Bandung: The Role of Self-Identification as a Mediator - Wiyono, Darul; Ambiapuri, Ema; Parwitasari, Nuraini; Tedi, Edi (Jurnal Manajemen, 2024)
This study aims to investigate the impact of Diversity and Inclusion Policy Strategy (DIPS) on enhancing team creativity in star-rated hotels in Bandung, with self-identification as a mediator and leader support as an optimizing factor. The research methodology employed is quantitative, utilizing survey techniques and case studies, involving 339 respondents from 183 four and five-star hotels. The sample was obtained using the Slovin formula with a 0.05 margin of error, implemented through the Area Probability Sampling Technique, particularly employing a purposive sampling approach. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 3.0 application. The research findings indicate that DIPS has a positive and significant impact on self-identification and team creativity. Self-identification has also proven to be an effective mediator. Leader support plays an optimizing role in the relationship between DIPS and team creativity. Furthermore, specific findings regarding the impact of DIPS on self-identification and team creativity through specific pathways provide in-depth insights. The managerial implications of this research support the need for robust implementation of DIPS and effective leader support to create an innovative work environment and foster team creativity. These results can serve as guidance for management practitioners and contribute to the literature on diversity and inclusion policies, as well as team creativity in the hospitality sector